2014
DOI: 10.3389/fpsyg.2014.00761
|View full text |Cite
|
Sign up to set email alerts
|

Frontal lobe neurology and the creative mind

Abstract: Concepts from cognitive neuroscience strongly suggest that the prefrontal cortex (PFC) plays a crucial role in the cognitive functions necessary for creative thinking. Functional imaging studies have repeatedly demonstrated the involvement of PFC in creativity tasks. Patient studies have demonstrated that frontal damage due to focal lesions or neurodegenerative diseases are associated with impairments in various creativity tasks. However, against all odds, a series of clinical observations has reported the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 163 publications
1
36
0
1
Order By: Relevance
“…In sharp contrast with this finding, another noninvasive brain stimulation study reported that a hyperactivation of the prefrontal cortex was beneficial for creative production, suggesting that better cognitive control led to better creative ideas generation (Colombo, Bartesaghi, Simonelli, & Antonietti, ). In a similar vein, numerous studies on clinical disorders associated with inhibitory control deficits suggest that impaired cognitive control might facilitate original associations and stimulate creative ideas generation (see de Souza et al., ). We note, however, that these patients rarely exhibited specific deficits in inhibitory control.…”
Section: Limitationsmentioning
confidence: 97%
“…In sharp contrast with this finding, another noninvasive brain stimulation study reported that a hyperactivation of the prefrontal cortex was beneficial for creative production, suggesting that better cognitive control led to better creative ideas generation (Colombo, Bartesaghi, Simonelli, & Antonietti, ). In a similar vein, numerous studies on clinical disorders associated with inhibitory control deficits suggest that impaired cognitive control might facilitate original associations and stimulate creative ideas generation (see de Souza et al., ). We note, however, that these patients rarely exhibited specific deficits in inhibitory control.…”
Section: Limitationsmentioning
confidence: 97%
“…The table includes studies in patients that related creative abilities to an anatomical location of a lesion or neurodegenerative impairment. Case reports already described in a previous review [60] Progressive supranuclear palsy characterized by atrophy in frontal cortex, basal ganglia, and midbrain; RAT: remote associates task; SD: semantic dementia, that is, temporal variant of frontotemporal lobar degeneration characterized by predominantly temporal atrophy; TTCT: Torrance test of creativity thinking; VBM: voxel-based morphometry; VSLM: voxel-based lesionsymptom mapping analysis. a 'Pure' medial PFC refers to the subset of the medial group that had pure medial or orbitofrontal damage.…”
Section: Recent Cognitive and Neuroimaging Findingsmentioning
confidence: 99%
“…This test has been employed in both clinical and research contexts and provides scores of fluency (the number of productions), flexibility (the ability to provide different categories of productions), originality (the ability to create rare productions) and elaboration (the ability to enrich productions with details); all these creative domains being affected in ASP. It has been demonstrated that brain diseases can impair creative production (Schott, 2012;de Souza et al, 2014). More specifically, reduced creative performance has been related to prefrontal damages (de Souza et al, 2010).…”
Section: Case Historymentioning
confidence: 99%